Orthostatic intolerance with tachycardia (postural tachycardia syndrome) and without (hypocapnic cerebral hypoperfusion) represent a spectrum of the same disorder - Novak, Peter; Systrom, David M.; Witte, Alexandra; Marciano, Sadie P. (Frontiers in Neurology, 2024)
Background Spectrum of chronic orthostatic intolerance without orthostatic hypotension includes postural tachycardia syndrome (POTS), with orthostatic tachycardia and hypocapnic cerebral hypoperfusion (HYCH), without orthostatic tachycardia. This study compared autonomic, cerebrovascular, and neuropathic features of POTS and HYCH. Methods This retrospective study evaluated patients with orthostatic intolerance referred for autonomic testing. Analyzed data included surveys (Survey of Autonomic Symptoms, Compass-31, Neuropathy Total Symptom Score-6, Central Sensitization Inventory) and autonomic tests (Valsalva maneuver, deep breathing, sudomotor and tilt tests), cerebrovascular (cerebral blood flow velocity (CBFv) monitoring in the middle cerebral artery), respiratory (capnography), neuropathic (skin biopsies for assessment of small fiber neuropathy) and invasive cardiopulmonary exercise testing (iCPET). Results A total of 127 HYCH, 125 POTS, and 42 healthy controls were analyzed. Compared HYCH to POTS patients, there was no difference in the duration of symptoms, the prevalence of younger women, comorbidities, sensory and autonomic complaints, central sensitization syndrome, supine/standing norepinephrine levels, inflammatory markers and medical therapy except for gastrointestinal medication. Autonomic testing showed widespread but similar abnormalities in POTS and HYCH that included: reduced orthostatic CBFv and end-tidal CO2, preload failure (assessed in 16/19 POTS/HYCH), mild autonomic failure, and frequent small fiber neuropathy. Conclusion HYCH and POTS are syndromes of orthostatic intolerance with cerebral hypoperfusion associated with reduced orthostatic cerebral blood flow, hypocapnia, mild autonomic failure and small fiber neuropathy of a similar degree and distribution; except for tachycardia in POTS. Similarities in peripheral domain abnormalities that affect heart rate suggest that orthostatic tachycardia in POTS is driven by the central nervous system overcompensation of orthostatic challenge. These findings provide additional evidence that HYCH and POTS represent a spectrum of the same disorder. Reduced orthostatic cerebral blood flow is a key unifying feature of HYCH and POTS.